2000
DOI: 10.1152/jappl.2000.88.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle mass and intensity of isometric contraction on heart rate

Abstract: The purpose of this study was to determine the effect of muscle mass and the level of force on the contraction-induced rise in heart rate. We conducted an experimental study in a sample of 28 healthy men between 20 and 30 yr of age (power: 95%, alpha: 5%). Smokers, obese subjects, and those who performed regular physical activity over a certain amount of energetic expenditure were excluded from the study. The participants exerted two types of isometric contractions: handgrip and turning a 40-cm-diameter wheel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
2
27
1
7
Order By: Relevance
“…It has been hypothesised that isometric contractions of a greater muscle mass require an increased central and peripheral drive (Mitchell et al 1980;Gálvez et al 2000). Consequently, the cardiovascular control centres will be stimulated in parallel fashion with the motor cortex (Franke et al 2000), thus producing a larger increase in cardiovascular response (a likely stimulus for resting BP adaptation) through greater central command (Gálvez et al 2000).…”
Section: Table 2 Here Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesised that isometric contractions of a greater muscle mass require an increased central and peripheral drive (Mitchell et al 1980;Gálvez et al 2000). Consequently, the cardiovascular control centres will be stimulated in parallel fashion with the motor cortex (Franke et al 2000), thus producing a larger increase in cardiovascular response (a likely stimulus for resting BP adaptation) through greater central command (Gálvez et al 2000).…”
Section: Table 2 Here Discussionmentioning
confidence: 99%
“…Consequently, the cardiovascular control centres will be stimulated in parallel fashion with the motor cortex (Franke et al 2000), thus producing a larger increase in cardiovascular response (a likely stimulus for resting BP adaptation) through greater central command (Gálvez et al 2000). Further to this, evidence suggests that increased motor unit recruitment also enhances the exercise pressor response (Seals 1989) due to either greater physical deformation that stimulates the mechanoreceptors (Gálvez et al, 2000) and/or increased metabolite production activating the metaboreceptors (Iellamo et al 1999). However, since this study used a unique constant position isometric contraction style, direct comparisons to previous research, such as constant EMG isometric exercise are difficult.…”
Section: Table 2 Here Discussionmentioning
confidence: 99%
“…This occurs in the first 10 seconds of exercise 2 . Depending on the intensity and duration of the isometric contraction performed, the HR increases gradually, especially due to the sympathetic modulation of the ANS [2][3][4][5][6][7] . Some studies have reported that the improvements on muscle strength and the resistance training are safe for lowrisk patients [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The RMSSD index is often used to quantify parasympathetic modulation on the sinus node during both resting and exercise conditions (Malik et al 1996). Another well-known test of the autonomic nervous system is the evaluation of HR response patterns during isometric contractions (Hohnloser and Klingenheben 1998;Galvez et al 2000;Maciel et al 1987Maciel et al , 1989Iellamo et al 1997;Silva et al 1999). This active autonomic test has advantages over the kinds which take their measurements during rest, as interactions between the musculoskeletal and cardiovascular systems can be assessed non-invasively, for example, after ST of a speciWc muscle group.…”
Section: Introductionmentioning
confidence: 99%